Mat Pilates Exercise Increase Hip Flexibility in Young Adults with Obesity - Naufal Prima Wianto; Erna Setiawati; Dwi Pudjonarko; Tanti Ajoe Kesoema (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Background:Young adult with obesity may experience in decreased hip flexibility. Decreased hip flexibility can be caused by excessive fat mass around the joint, lack of physical activity, resulting in muscle stiffness. Flexibility can be improved by Mat Pilates exercises which combined static and dynamic movements. Objective:To prove increasing hip joint flexibility of young adult with obesity after doing Mat PilatesMethods:This study used experimental study with comparison group pre-test and post-test design. The participants were 38 young adults with obesity lived in Semarang selected by purposive sampling technique. The participants were divided into experiment group and control group. The experiment group was instructed to do Mat Pilates (3 times a week) for 4 weeks and the control group was instructed to do their usual activity. The hip flexibility was measured with sideward leg splits before and after experiment. The collected data was analyzed using paired t, independent t test.Results:There was a significant increase in the value of sideward leg splits after doing Mat Pilates (p < 0,05), from 98,46±9,73 to 112,82±11,22 for left sideward leg splits and from 99,63±10,20 to 111,39±12,99 for right sideward leg splits. The increase in the value of sideward leg splits in the experiment group was higher than the control group (p < 0,05). It was occured for both left sideward leg splits and right sideward leg splits.Conclusion:Mat Pilates increased hip joint flexibility of young adult with obesityBackground:Young adult with obesity may experience in decreased hip flexibility. Decreased hip flexibility can be caused by excessive fat mass around the joint, lack of physical activity, resulting in muscle stiffness. Flexibility can be improved by Mat Pilates exercises which combined static and dynamic movements. Objective:To prove increasing hip joint flexibility of young adult with obesity after doing Mat PilatesMethods:This study used experimental study with comparison group pre-test and post-test design. The participants were 38 young adults with obesity lived in Semarang selected by purposive sampling technique. The participants were divided into experiment group and control group. The experiment group was instructed to do Mat Pilates (3 times a week) for 4 weeks and the control group was instructed to do their usual activity. The hip flexibility was measured with sideward leg splits before and after experiment. The collected data was analyzed using paired t, independent t test.Results:There was a significant increase in the value of sideward leg splits after doing Mat Pilates (p < 0,05), from 98,46±9,73 to 112,82±11,22 for left sideward leg splits and from 99,63±10,20 to 111,39±12,99 for right sideward leg splits. The increase in the value of sideward leg splits in the experiment group was higher than the control group (p < 0,05). It was occured for both left sideward leg splits and right sideward leg splits.Conclusion:Mat Pilates increased hip joint flexibility of young adult with obesity